Evalusi Pelaksanaan Program Larasita di Kabupaten Grobogan - Arif Nur Rohkim; Purwoko .; Wiwik Widayati (Journal of Politic and Government Studies, 2013)
AbstractsConcerning to emerge The Good Governance, bureaucrate performance has the mainrole, especially solving every problems popped out among civic social life, consideringfunction of state institution has the role to accomodate the needs of its people. Mostfrequently problems could be varied from different aspects, such as land-affairs, education,economy, demography, transportation, etc. Those problems will be an responsibility for all ofstate institution in the process to reach the development of welfare in every aspect.In thehuman life, land was the one of important things, because of not only as regard to economyproblems. But also related to civil rights, particularly within increasingly growth ofdevelopment year by year. For reaching the law certainly and law protection. In theowership or utilizing of land, written regulation are needed, printed completely andconsistantly done so that land conflict could be avoided.One of govermental institution which succed n implemting the e-goverment system asthe one of basic public service in the national land institutin ( BPN ). Which also bringing theprogram called larasita ( Public service for land-certification ) organized as mobile landaffairsoffice which have similar main duty and function with obtained in land-affairs office.Larasita operated the picking ball up system among the people.Keyword : Public Services, Land-affairs, Larasita.